Markers of innate immune activity in patients with type 1 and type 2 diabetes mellitus and the effect of the anti‐oxidant coenzyme Q10 on inflammatory activity. (August 2014) - Brauner, H.; Lüthje, P.; Grünler, J.; Ekberg, N. R.; Dallner, G.; Brismar, K.; Brauner, A.
Summary Major long‐term complications in patients with diabetes are related to oxidative stress, caused by the hyperglycaemia characteristic for diabetes mellitus. The anti‐oxidant coenzyme Q10 (CoQ10) has therefore been proposed as a beneficial supplement to diabetes treatment. Apart from its anti‐oxidative function, CoQ10 appears to modulate immune functions by largely unknown mechanisms. The aim of this study was therefore to investigate the effect of CoQ10 on antimicrobial peptides and natural killer (NK) cells, both innate immune components implicated in the pathogenesis of diabetes and diabetes‐associated long‐term complications such as cardiovascular disease. We determined serum levels of antimicrobial peptides and the phenotype of NK cells isolated from peripheral blood of patients with type 1 (T1DM) or type 2 diabetes mellitus (T2DM) and from healthy controls. In addition, the same parameters were determined in diabetic patients after a 12‐week period of CoQ10 supplementation. Two antimicrobial peptides, the human cathelicidin antimicrobial peptide (CAMP) and the human beta defensin 1 (hBD1), were reduced in serum from patients with T1DM. This defect was not reversible by CoQ10 supplementation. In contrast, CoQ10 reduced the levels of circulating hBD2 in these patients and induced changes in subset distribution and activation markers in peripheral NK cells. The results of the present study open up novel approaches in the prevention of long‐term complications associated to T1DM, although further investigations are needed.